2021
DOI: 10.5539/ijef.v13n2p25
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Expenditure on Economic Growth in Algeria

Abstract: The present study aims to investigate the impact of health expenditure on economic growth in Algeria for the period 1960-2016. Using data from the World Bank database, the Autoregressive Vector model and Granger causality, findings show that health expenditure positively affects economic growth in the short term; which means that the study’s hypothesis is proved. The results therefore reveal the increasing importance of investment in the health sector in order to improve economic growth indicator in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ramirez et al (1998) affirm that human development facilitates countries to move into virtuous groups. Many empirical studies specifically Ranis (2004), Kaur (2013), Saha (2013), Chakraborty and Krishnankutty (2012) and Menon (2017) investigating the relationship between human development and economic growth have confirmed that human development leads to economic growth.…”
Section: Relationship Between Economic Growth and Human Developmentmentioning
confidence: 99%
“…Ramirez et al (1998) affirm that human development facilitates countries to move into virtuous groups. Many empirical studies specifically Ranis (2004), Kaur (2013), Saha (2013), Chakraborty and Krishnankutty (2012) and Menon (2017) investigating the relationship between human development and economic growth have confirmed that human development leads to economic growth.…”
Section: Relationship Between Economic Growth and Human Developmentmentioning
confidence: 99%
“…It has also been suggested that too stringent firing costs may strengthen the bargaining power of incumbent workers to an extent that reduces incentives for productivity-enhancing investment by employers (Caballero and Hammour 1996). However, the view that curtailing the extent of labour market protection might lead to better economic outcomes, including productivity 17 See, among others, Weil (2006), Bloom and Canning (2008), Kumar and Kober (2012) and Saha (2013).…”
Section: New Digital Technologies Such As Artificial Intelligence (Ai...mentioning
confidence: 99%